(untitled) (European Journal of Marketing and Economics, 2020)
This research examines the current reality of the sustainable cultural development, in the Cotacachi –Cayapas Ecological Reserve and its surroundings, part of the UNESCO Global Geoparks (2019), as a world heritage sight located in South America, in the inter-Andean region of the Republic of Ecuador. The diverse cultural and ethnic focusing on the situation of indigenous and peasant people, looking at the processes of their self-awareness, validation, and empowerment. The problems faced by this community are diverse in terms of their empowerment, low levels of education, low levels of economic development, and social, cultural and political discrimination. Their relationships are not stable and their incomes are variable, because they depend on farming and producing livestock on their small plots and the precarious nature of available work in their rural environment. The research enables us to conclude that participation in organizational groups and processes has strengthened the capacity of leadership to collaborate more actively and effectively in the progress and development of their indigenous and peasant communities. This, in turn, enhances success of their projects and makes possible the administration of public and private partnerships that permit social and institutional recognition, contributing to improvement in their standard of living and quality of life and to finds and alternative sustainable economy model based on a cultural tourism.